Associations between dietary flavonoid intake with hepatic steatosis and fibrosis quantified by VCTE: evidence from NHANES and FNDDS - Xie, Ruijie; Zhang, Ya (Nutrition, metabolism and cardiovascular diseases, 2023)
Background and aim - Flavonoids are natural products of plant origin and have been shown to be beneficial for nonalcoholic fatty liver disease (NAFLD) in animal studies. However, relevant epidemiological evidence is still lacking, and the relationship between flavonoid and subclass intake with quantified hepatic steatosis and fibrosis has not been investigated. - Methods and results - This study was based on the Food and Nutrient Database for Dietary Studies (FNDDS) expanded flavonoid intake database and the National Health and Nutrition Examination Survey (NHANES) 2017-2018 and included a total of 4113 participants with vibration-controlled transient elastography (VCTE) data. Multiple logistic regression was used to assess linear relationships between flavonoids and hepatic steatosis and fibrosis. Smoothed curve fit and a generalized additive model were used to investigate the non-linear relationship, and a two-tailed linear regression model was used to find potential inflection points. Of the 4113 participants, 1045 (25.41%) were diagnosed with NAFLD. After adjusting for energy and major non-dietary covariates, significant linear negative correlations were observed between total flavonoids and CAP [-1.53 (−2.59, −0.47)] and LSM [-0.17 (−0.27, −0.07)]. After adjusting for all covariates, flavones had the strongest and most significant negative association with hepatic steatosis [-1.98 (−3.79, −0.17)]. The results of smooth curve fitting and subgroup analysis demonstrated gender differences, and threshold effect analysis further identified a U-shaped relationship and inflection point between flavonoid intake and hepatic steatosis (infection point: 287.25 mg/d). - Conclusions - Our findings suggest negative associations between flavonoid and subclass intake with hepatic steatosis and fibrosis.
Online verfügbar: 10. März 2023, Artikelversion: 13. Mai 2023
Gesehen am 08.11.2023